MICROPLASTICS IN SOILS: A REVIEW OF ENVIRONMENTAL RISKS (Scientific journal of the Fergana State University, 2025)
High production rates, low plastic recycling levels, and the long lifespan of plastics have led to significant accumulation of the material in the environment. This includes plastic fragments